Needs must when the devil drives - Migration of an entire university to digital teaching - Julia Nitsche; Jan Smetana; Tonja Kochanek; Theresa S. Busse; Sven Kernebeck; Angelika Taetz-Harrer; Michaela Zupanic; Mona Eulitz; Jan Ehlers (Forum Neue Medien in der Lehre Austria, 2021)
This study describes how the pandemic and its need for digitization catalyzed broadly implemented further education at the University of Witten/Herdecke. The empirical data consist of 117 courses for the training of 320 university members. In addition, 424 students were surveyed on the perception of digital teaching. It became evident that even though technical knowledge was transferred successfully, the didactic implementation left room for improvement. The results of this study stress that a wide range of training opportunities support the use of technology enhanced learning as well as collaboration between faculty experts, IT professionals and educational developers.